Increase in the Lipopolysaccharide Activity and Accumulation of Gram-Negative Bacteria in the Stomach With Low Acidity. Issue 7 (21st July 2020) - Sano, Masaya; Uchida, Tetsufumi; Igarashi, Muneki; Matsuoka, Takashi; Kimura, Moto; Koike, Jun; Fujisawa, Mia; Mizukami, Hajime; Monma, Makiko; Teramura, Erika; Yoshihara, Shiho; Sato, Hirohiko; et al.
Abstract : INTRODUCTION: Lipopolysaccharides (LPSs) of Gram-negative bacteria (GNB) are highly toxic and induce inflammation. Therefore, we investigated both the LPS activity and composition of GNB in the gastric fluid (GF) to assess the potential toxicity of them accumulated in the stomach. METHODS: GF and saliva samples were obtained from 158 outpatients who were undergoing upper gastrointestinal endoscopy and 36 volunteers using a nasogastric tube. The LPS activity was measured by assay kits including recombinant Factor C or Limulus amebocyte lysate. To assess the bacterial composition in the samples, a 16S ribosomal DNA-based operational taxonomic unit analysis was performed. We focused on the genera representing >0.1% of the whole microbiota. RESULTS: We found a high LPS activity in the GF samples with weak acidity (approximately > pH 4), whereas little/no activity in those with strong acidity (approximately < pH 2). Spearman test also demonstrated a close correlation between pH and LPS in those samples ( r = 0.872). The relative abundance of GNB in the saliva showed no significant difference between the subject groups with weak- and strong-acidity GF. In addition, in the subjects whose GF acidity was weak, the GNB abundance in the GF was almost the same as that in the saliva. By contrast, in the subjects whose GF acidity was strong, the GNB abundance in the GF was significantly lower than that in the saliva. DISCUSSION: GNB that have recently moved from the oral cavity might account for the prominent LPS activity in a stomach with weak acidity.